Complete mitochondrial genome of Sebastes taczanowskii (Scorpaenidae, Scorpaeniformes) from the East Sea, Korea. (2nd September 2016) - Jang, Yo-Soon; Kim, Sung; Kim, Ki-Yong; Park, Jeong-Ho
Abstract: Sebastes taczanowskii is a subarctic species in the north-western Pacific Ocean. To obtain mitochondrial DNA sequences for phylogeny, the complete mitogenome (16 452 bp in length) of S. taczanowskii was constructed using next-generation sequencing. The circular mitogenome contains 13 protein-coding genes (PCGs), 2 rRNAs, 22 tRNAs and the control region, for which gene structure and positions were similar to those of other Scorpaenidae. The complete mitogenome composed of 27.8% A, 26.5% T, 17.3% G and 28.5% C, with a slight AT bias (54.3%). All PCGs use a typical start codon, ATG, except COX1 (GTG). The terminal codon of PCGs was mainly TAR, with the exceptions of ND4 (AGA) and Cytb (incomplete codon, T). Sebastes taczanowskii was clearly divided from other Scorpaenidae in the phylogenetic tree using 2 rRNA and 13 PCGs. The mitogenome of S. taczanowskii can be useful for constructing the molecular phylogenetic tree within Scorpaenidae.